If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(2x+4)=-8x+16
We move all terms to the left:
-4(2x+4)-(-8x+16)=0
We multiply parentheses
-8x-(-8x+16)-16=0
We get rid of parentheses
-8x+8x-16-16=0
We add all the numbers together, and all the variables
-32!=0
There is no solution for this equation
| 3x+6=2×+12 | | X^2-3x+16=-4 | | 11y-7y-11=61.32 | | 3x-x/2=40 | | -2x+8=1x-8 | | 4+10c=c-1 | | 4b+1=6+12b | | 3x+6=2×+11 | | p+7/3=-31/6 | | -186=6x+5(4x-6) | | 2y+8=y+15 | | 2+4x-4=22 | | -x-53=-8x+4-12x | | 4^2-X*3=27 | | 16x-5-8x=-17+2x | | t/5-4=3 | | 7v/5=45 | | 3x+4=2+1 | | 9^(x+2)=240+9^x | | 8x-38=-2x-8 | | -12+.25x+40=35 | | t65=325 | | 63*x/36+41=48 | | 6x+12=-6x=12 | | 2z^2+8z+40=0 | | 16x+28=76 | | -5r(r+7)=-92 | | 20x*0.1=9 | | 4x+3(2x-4)=8 | | 22=p-(-13) | | 120=-20n | | m+2=−m+32 |